“Where You Are Accepted, You Blossom”: Toward Care Ethics in Jazz Historiography - Blais-Tremblay, Vanessa (Jazz & Culture, 2019)

Jazz, gender, historiography: a case study of the "Golden Age" of jazz in Montreal (1925-1955) - Blais-Tremblay, Vanessa (Université McGill, 2018)
This dissertation maps the interaction between jazz, identity, modernity and nation during the so-called "golden age" of jazz in Montreal (1925-1955). Drawing on the fields of musicology, women's studies (black feminist theory and feminist research methods in particular), critical dance studies, and cultural studies, this project provides a critical re-writing of the history of Montreal jazz, one which acknowledges various roles that racialized and ethnicized women played in the shaping of modern identities, pleasures and sounds in Quebec. Montreal's particular status as a "showtown" makes it a rich laboratory to study the collaborative creative relationships between jazz music and dance on the black variety stage in the first half of the twentieth century. I also map the specific parameters that articulate the discursive relationship between jazz and vice, in particular as these relate to the gendered and racialized embodiment of morality in interwar Quebec. Finally, this dissertation produces the first extensive biographical accounts and critical listening of several prominent Montreal-based female jazz artists, including pianists Vera Guilaroff and Ilene Bourne, all-girl groups such as The Spencer Sisters and the Montreal Melody Girls Orchestra, black women performers such as Tina Baines Brereton, Bernice Jordan Whims, Marie-Claire Germain, Mary Brown, Natalie Ramirez, as well as piano teacher Daisy Peterson Sweeney and dance teachers Ethel Bruneau and Olga Spencer Foderingham.

Femmes et jazz dans le Québec de l’entre-deux-guerres : entre le récit historique, les archives et le passé - Blais-Tremblay, Vanessa (Les Cahiers de la Société québécoise de recherche en musique, 2017)
Cet article porte sur les rôles que les femmes ont joué dans le développement d’une scène jazz à Montréal. Les archives témoignent de l’importance des pianistes Vera Guilaroff et Ilene Bourne, de l’enseignante de piano Daisy Peterson Sweeney, des enseignantes de danse Olga Spencer Foderingham et Ethel Bruneau, ainsi que des danseuses de variétés dans le développement de la plus grande scène jazz du Canada au cours de la première moitié du xxe siècle. Cet article contextualise la présence des femmes dans ces espaces performantiels précis (le piano, l’enseignement, la danse) et explore les processus historiographiques liés à leur exclusion des récits historiques.

Life notations of Daisy Sweeney: reflections of othermothering, musicianship and Montreal - Campbell, Arlene (Université York, 2012)
The life story of Mrs. Daisy Sweeney, an African Canadian native of Montreal, Quebec, helps fill a void in the historical documentation of Montreal Blacks (especially female elders). Of particular significance is her prominence as a music educator and othermother during her life. The current literature on African Canadian othermothering experiences is not synonymous with both White or African American females and inclusion of their voices in academic, as well as mainstream spaces, is virtually non-existent. This dissertation asks: What did it mean to be a first generation 'Negro' working class bilingual female in a largely hostile White francophone Quebec metropolis in the early 20th Century? How can her narratives help shape and inform life history and African Canadian othermothering research? My sojourn with Mrs. Daisy Sweeney referenced African centered epistemology in my conceptual understanding of herself and community mothering. Capturing her conversations meant engaging with multiple methodologies articulated through African oral traditions, life history, archival canons and interdisciplinary inquiries. It is striking to note that there were not only certain tensions associated with memory loss and physical limitations (prompted by the aging process) that destabilized and enriched our 'interactive' communication, but also revealed a rupture and reversal of the participant/researcher dynamic. In spite of blatant racial discrimination that plagued Montreal's Black communities during that time, Daisy Sweeney fulfilled a life-long dream and taught hundreds of children the canon of classical piano for over 50 years. She lived her voice through her music, finding ways to validate her own identity and empowering others in the process. She used the musical stage as her platform to draw invaluable connections between race, gender, language and social class. Daisy Sweeney's generation of othermothers is dying out and, as the carriers of culture, the urgency to tell their stories must be emphasized. The account respects, reclaims and reflects those voices. It is time to write in African Canadian female elders and diversify the exclusionary genre of life history and archival research.

Ethel Bruneau: Montreal’s Rhythm Tap Legend - Lys, Stevens (Dance Collection Danse, 2011)